PENGARUH DISKON DAN FLASH SALE ONLINE SHOP TERHADAP MINAT BELI ONLINE PADA E-COMMERCE SHOPEE (STUDI KASUS PADA MAHASISWA MANAJEMEN UPGRIS) - Rahmad Amin Huda; Putri Rahmawati, Rauly Sijabat (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research was conducted based on the researcher's desire to find out the effect of discounts and flash sales in online shops on UPGRIS management students' buying interest. This type of research is a quantitative method and uses a saturated sample sampling method of 29 students. The results obtained from the T test show that variable X1 has a positive effect on variable Y while Variable by discounts and flash sales while the other 67% is influenced by other variables.